Islamic Law Review of Sharia Cooperative Practices in Indonesia - Judijanto, Loso; Sufriaman, Sufriaman; Muhammadong, Muhammadong; Mu'min, Halek (West Science Islamic Studies, 2024)
This paper examines the practices of Sharia cooperatives in Indonesia through an Islamic law perspective, focusing on their adherence to Sharia principles, the effectiveness of existing legal frameworks, and the operational challenges they face. Utilizing a comprehensive literature review, the study reveals that while Sharia cooperatives aim to provide ethical financial solutions, many struggle with compliance due to inadequate understanding of Islamic finance, regulatory ambiguities, and governance issues. The findings highlight the importance of enhancing regulatory clarity, establishing robust Sharia supervisory bodies, and fostering continuous education among cooperative managers and staff. By addressing these challenges, Sharia cooperatives can better align their practices with Islamic law and contribute to the broader Islamic finance ecosystem in Indonesia.